Magnetization transfer ratio in peripheral nerve tissue: does it depend on age or location? - Hayes, Jennifer; Kästel, Thorsten; Jende, Johann; Bendszus, Martin; Heiland, Sabine (Investigative radiology, 2018)
Magnetization transfer contrast imaging provides indirect information on the concentration of “bound” water protons and their interactions with “free” water molecules. The purpose of this study is to analyze location- and age-dependent changes in the magnetization transfer ratio (MTR) of lower extremity nerves.